Why do women's cooperative societies languish? A study of selected societies in Kottayam, Kerala - Nisha Velappan Nair & John S. Moolakkattu (Asian Journal of Women’s Studies, 2015)
Kerala has had a long history of cooperatives starting from the pre-independence era. The idea of women’s cooperatives came much later, with the earliest ones coming into being only after 1975. This study draws on both primary and secondary data, focusing on the challenges faced by women’s cooperative societies (WCSs) in Kottayam District in Southern Kerala. Most women’s cooperatives function by limiting their operations to small scale banking activities and enlisting men’s participation in various ways. The paper concludes that the scope of empowerment of women through women’s cooperatives is severely constrained by the way property rights and gender relations are structured in the state and the manner in which local male politicians have manipulated the societies for partisan ends.